Determinants of consumers' online purchase intention - Campino, José (2023)
This study identifies the main variables that influence consumers' intention to purchase online. The variables analyzed were trust, design, value proposition, delivery, protection and guarantee and finally the payment methods. Data collection was carried out through an anonymous questionnaire made available online which obtained 182 responses. The results showed the relevance of trust, value proposition and payment for purchase intention. The results of the study also demonstrated the different impact of the variables on consumers aged 25 years or less compared to the rest of the older age groups. In these cases, it was evident that the value proposition has an impact on the purchase intention of younger consumers and the different forms of payment impact the intention of older age groups.